1998
DOI: 10.1007/bfb0057946
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous (Time-Warp) versus synchronous (Event-Horizon) simulation time advance in BSP

Mauricio Marín

Abstract: This paper compares the very fundamental concepts behind two approaches to optimistic parallel discrete-event simulation on BSP computers [10]. We refer to (i) asynchronous simulation time advance as it is realised in the BSP implementation of Time Warp [3], and (ii) synchronous time advance as it is realised in the BSP implementation of Breathing Time Buckets [8]. Our results suggest that asynchronous time advance can potentially lead to more efficient and scalable simulations in BSP. IntroductionAs BSP is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Those include the synthetic work-load PHold, Wind energy electricity generation systems, hard-particles models, Web crawlers, and a large toriodal queuing network. In all cases, specially in regular systems, we have observed that our prediction methodology is very effective in practice (this claim is supported by the results in [3,4]). …”
Section: Discussionsupporting
confidence: 76%
“…Those include the synthetic work-load PHold, Wind energy electricity generation systems, hard-particles models, Web crawlers, and a large toriodal queuing network. In all cases, specially in regular systems, we have observed that our prediction methodology is very effective in practice (this claim is supported by the results in [3,4]). …”
Section: Discussionsupporting
confidence: 76%